A REVIEW ON SUSTAINABILITY AS AN OPTIMIZATION PROBLEM - Mohamad Zain, Shaharir Mohamad Zain (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2017)
We show that the present policy of sustainability is a solution of an optimization problem. Then we criticize the present concept of optimization by showing that it is not comprehensive enough to cover the spiritual dimension of man needed to handle sustainability and it also inherits values from capitalism and related philosophies which are known to be incompatible with sustainability. Accordingly, the concept of optimization is replaced by a new definition of the best policy based on an Islamic value, which we call wusta. We then propose a new concept of sustainability which we hope to formulate its corresponding multiobjective wustaization planning model in the near future.